Evaluation Of Piper Sarmentosum (Ps) Leaves Extracts As Green Inhibitor For Corrosion Of Mild Steel In 0.5 M Hcl Solution - Rozuli, Nurul Adilla (2019)
This study focused on the evaluation of Piper sarmentosum (PS) leaves extracts isolated using ethanol (PSE), water (PSW), ethyl acetate (PSA) and n-hexane (PSN) as corrosion inhibitors for mild steel in 0.5 M HCl solution. In this study, PSE and PSW contained the highest content of TPC, TFC and antioxidants as compared to other extracts. Electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PD) and electrochemical noise measurement (ENM) were employed to determine the corrosion inhibitive properties of the extracts. Based on EIS data, it was revealed that PSE and PSW provided the highest inhibition efficiency of 93.24% and 93.00%, respectively at 1000 ppm. Additionally, PD analysis demonstrated that PSE and PSW act as a mixed type corrosion inhibitor, predominantly mitigating the anodic reaction. Moreover, PSE and PSW adsorption mechanism obeyed Langmuir isotherm model illustrating a spontaneous semi-physisorption and/or semi-chemisorption adsorption process. SEM analysis showed the improvement of the surface morphology of mild plates in the presence of both inhibitors. The present study also investigated the coating resistance characteristics of hybrid sol-gel matrices prepared using APTES and TEOS deposited on mild steel adopting the dip-coating technique. Mild steel surfaces treated with inhibitors doped hybrid sol-gel coatings were found to be more hydrophobic compared to bare mild steel surface.